Truth, lies and fiction: exploring the boundaries of documentary - Koba, Siyabonga (My University, 2011)
Like all filmic modes documentaries are ideological artistic constructions and according to Bill Nichols (2001: 38) they carry more influence than fiction because we assume that documentary sounds and images are authentic. According to John Ellis (2005: 1) documentaries work because they generate in us a belief of truth that what we see on the screen can be trusted. Through its ability to elicit trust from its audiences, the documentary has set itself apart from the fiction which has also been termed “fabrication” (Renov, 1993: 7). Unlike fiction, the documentary does not stage, fabricate or create life but simply represents it (Nichols, 2001: 20). Fiction therefore becomes the antithesis of documentary and documentary becomes the antithesis of the fiction and all that it is known for: fabrication and falsification. Carroll Noel agrees that (1996: 255) the fiction/nonfiction dichotomy is used to “commend or disparage items as true or false.” Drawing from the complimentary film component as a case study and a framework of theoretical ideas, this paper suggests that without such perceived conditions of difference and associations of truth the documentary film by itself might be no more truthful than fiction. What separates these two forms is the way we look at them.
Keywords: Documentary films